Empowerment Of Human Resources As A Strategy To Increase Regional Economic Competitiveness - Tiwi Nurhastuti; Elmiwati , Elmiwati (PT. ALHAFI BERKAH INDONESIA, 2025)
This research examines human resource empowerment as a strategy to enhance regional economic competitiveness in Indonesia. Human resource empowerment has become a crucial factor in driving local economic growth and creating regional competitive advantages. Using a qualitative method with a descriptive approach, this research analyzes human resource empowerment programs and their impact on regional economic development. The results indicate that successful human resource empowerment is supported by the integration of training programs, education, and skills development aligned with local labor market needs. Improved human resource quality positively impacts work productivity, innovation, and adaptability to economic changes. This study concludes that human resource empowerment needs to be conducted in a structured and integrated manner involving various stakeholders to create an effective human resource development ecosystem that supports regional economic competitiveness.